Not just contact sports: significant numbers of sports-related concussions in cycling - Helmich, I.; von Götz, D.; Emsermann, C.; Xuanjin, F.; Griese, A.; Lauterbach, I.; Lausberg, H. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Although sports-related concussions (SRCs)/mild traumatic brain injuries in contact sports have recently received much attention, investigation of SRCs in cycling - a sport yielding some of the highest percentages of SRC - remains strikingly limited. In particular, rates of incidence, cycling-specific causes, and potential long-term effects of SRC have not been examined in this sport. Here, a retrospective online survey was used to investigate the incidence and potential long-term effects of SRCs among cyclists. METHODS: A cycling-specific questionnaire was developed and administered to 2792 cyclists via an online survey. First, participants were asked about their acute symptomatology, and secondly, cycling-specific items and concussion history were addressed. RESULTS: Of the 999 cyclists whom completed the questionnaire, 23.8% had experienced a concussion. Incidence of concussion was significantly higher in cyclists who were club members, who cycled more than 200 kilometers per week, and who wore a helmet. Cyclists with a history of concussion complained significantly more often about headaches, pressure in the head, sensitivity to light, confusion, and irritability. CONCLUSIONS: Concussions in cycling are a serious injury with a high incidence relative to other sports. Although wearing a helmet reduces the risk of severe brain injury, interesting, the present results show a relation between helmet use, participation in cycling clubs, and increased concussion incidence. These data are in line with the growing number of findings showing that athletes with a history of concussion report more symptoms.